Identification of OLED Degradation Scenarios by Kinetic Monte Carlo Simulations of Lifetime Experiments - Hauenstein, Christoph; Gottardi, Stefano; Torun, Engin; Coehoorn, Reinder; van Eersel, Harm (Frontiers in Chemistry, 2022)
We show how three-dimensions kinetic Monte Carlo simulations can be used to carry out an operational lifetime study of thermally activated delayed fluorescence (TADF) organic light-emitting diodes (OLEDs) and to deduce the sensitivity to various degradation scenarios. The approach is demonstrated for an experimentally well-characterized efficient green-emitting device. The simulation workflow includes an equilibration phase, an equilibrated pristine state phase and a degradation phase. Acceleration of the simulations by extrapolation from simulations at large current densities makes the simulation time realistically feasible. Such a procedure is also often followed in experimental studies. Degradation is assumed to be triggered by exciton-polaron quenching and exciton-exciton annihilation processes. A comparison of the simulated and experimental time-dependence of the luminance decay provides the probability that a degradation-triggering event leads to the formation of a degraded molecule. For the TADF OLED that has been studied, this parameter is only weakly dependent on the assumed scenario, provided that the degraded molecules are assumed to form trap sites, and is found to be ∼ (0.2–0.7) × 10 −9 . The approach is expected to enable systematic in silico studies of the operational lifetime and its sensitivity to the material composition, layer structure, charge carrier balance, and the use of refined device principles such as hyperfluorescence.